Transthoracic Doppler echocardiographic analysis of phasic coronary blood flow velocity in hypertrophic cardiomyopathy. - Crowley, J. J. (1997)
OBJECTIVE: To use transthoracic Doppler echocardiography to assess coronary blood flow non-invasively in patients with hypertrophic cardiomyopathy. DESIGN: High frequency transthoracic Doppler echocardiography was used to assess resting phasic coronary velocity patterns in patients with hypertrophic cardiomyopathy and to define the relation between coronary flow patterns and clinical, echocardiographic, and haemodynamic manifestations of this condition. SETTING: A tertiary referral cardiothoracic centre. METHODS: Fifteen patients (10 men and five women, mean (SD) age 49 (10.3) years) with asymmetric hypertrophic cardiomyopathy underwent high frequency (5 MHz) transthoracic Doppler echocardiographic assessment of the left anterior descending coronary artery. In addition, standard two dimensional echocardiography was performed. The results were compared with 16 normal participants (nine men and seven women, mean age 61.2 (10.7) years) who had no evidence of cardiac disease. RESULTS: Biphasic diastolic predominant coronary artery blood velocity profiles were obtained in all patients and controls. Systolic peak blood velocity and velocity time integral were significantly reduced in the hypertrophic cardiomyopathy group compared with controls (11.3 (15.8) cm/s and 1.09 (1.78) cm v 20.5 (13.1) cm/s and 4.23 (2.80) cm, respectively, P < 0.05). A reversed pattern of systolic blood flow velocity was found in three patients with severe anterior wall and septal hypertrophy. During diastole there was prolongation of the diastolic acceleration (203 (53) ms v 110 (60) ms in controls, P < 0.05) and deceleration times (487 (200) ms v 210 (90) ms in controls, P < 0.05). There was no significant difference between those with and without symptoms or a left ventricular outflow tract gradient. CONCLUSIONS: Patients with hypertrophic cardiomyopathy have abnormal systolic and diastolic coronary flow profiles at rest when measured by transthoracic echocardiography.